Peningkatan efisiensi administrasi desa melalui implementasi teknologi informasi OpenSID di Kelurahan Air Putih - Fitriana, Nur; Mazhar, Kawish Behzad; Azhar, M. Ibnu Luthfi (Universitas Hamzanwadi, 2023)
Information Systems (IS) have become an essential tool in supporting management and services at the community level. In the context of RW 06, Kelurahan Air Putih, Pekanbaru, Riau, the need for an efficient and effective system has become increasingly urgent. Therefore, through the Real Work Lecture Program (KKN) UMRI Smart, we have adopted and adapted OpenSID to meet the needs of RW 06, especially RT 01 to RT 06. The primary objective of this adaptation was to modernize administration and enhance information services for residents. By integrating technology and a participatory approach, we aim to create a more informed and connected environment. The adjustments made were not only technical but also pertaining to the content and the manner of presenting information, thus making it relevant to the context of the RW and RT in Kelurahan Air Putih. The results of the activities indicate that OpenSID has successfully increased administrative efficiency in RW 06 by facilitating access to information and population data management. The conducted training sessions effectively enhanced users' understanding and skills in system operations. The survey conducted among 6 RTs showed a positive response, with an average of 60% of respondents feeling at ease interacting with the system interface. In contrast, only about 16.67% did not share this sentiment, and 23.33% were neutral. In particular, the majority of respondents considered the training materials helpful, with a high level of satisfaction regarding the system's performance and functions. Nonetheless, there were several challenges, such as user adaptation to new technology, as seen from the percentage feeling 'Moderate' in certain aspects, and the need for additional feature development to increase user convenience. This activity provides insights into the benefits and challenges of implementing OpenSID at the RW level and highlights the importance of ongoing training and support for the success of digital transformation in local communities.